2020
DOI: 10.1002/cplu.202000257
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalent Chemistry as a Facile Route to Unusual Main‐Group Thiolate Assemblies and Disulfide Hoops and Cages

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
0
23
0
4
Order By: Relevance
“…Dynamic covalent sulfur exchange cascades before or during direct translocation across the plasma membrane into the cytosol appear to dominate with synthetic delivery systems. , HIV entry is an established example for inhibitable dynamic covalent sulfur exchange on cell surfaces followed by membrane fusion, while dynamic covalent sulfur exchange with proteases in endosomes and lysosomes, such as cathepsins, can, perhaps, be considered as arguably borderline examples for thiol-mediated uptake combined with endocytosis . More precise mechanistic information is often missing, particularly for direct translocation, also because dynamic covalent chemistry dramatically complicates, and discourages, target identification. However, it is also this dynamic covalent chemistry that makes thiol-mediated uptake so unique and attractive, particularly from the viewpoint of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic covalent sulfur exchange cascades before or during direct translocation across the plasma membrane into the cytosol appear to dominate with synthetic delivery systems. , HIV entry is an established example for inhibitable dynamic covalent sulfur exchange on cell surfaces followed by membrane fusion, while dynamic covalent sulfur exchange with proteases in endosomes and lysosomes, such as cathepsins, can, perhaps, be considered as arguably borderline examples for thiol-mediated uptake combined with endocytosis . More precise mechanistic information is often missing, particularly for direct translocation, also because dynamic covalent chemistry dramatically complicates, and discourages, target identification. However, it is also this dynamic covalent chemistry that makes thiol-mediated uptake so unique and attractive, particularly from the viewpoint of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The family of biphenyl disulphides is important due to their applications as drugs, [15] sensors, [16] lubricants, [17] polymers; [18–21] source of PhS substituents in organic reactions [22, 23] and precursors for supramolecular systems [24–26] . Recently we showed that di‐ p ‐tolyl disulphide (4‐CH 3 ‐PhS) 2 absorbs the energy of compression by phase transitions and conformational transformations [27] .…”
Section: Polymorph α[31] β γmentioning
confidence: 99%
“…Pioneering work by Johnson and co-workers confirmed operational thiol/ate exchange on arsenic, antimony, and bismuth relays in dynamic covalent macrocyclic architectures. 32 , 33 In chemical biology, FlAsH probes 34 , 35 and molecular walkers exchanging along thiol tracks 36 are among the highlights. With regard to cellular uptake, facilitated, glutathione (GSH)-dependent penetration of bismuth has been proposed.…”
Section: Introductionmentioning
confidence: 99%